Pengenalan dan Pelatihan Asesmen Kompetensi Minimum (AKM) Bagi Siswa Kelas VI SD: Pengabdian - Puspawati; Nur Khojin; Slamet Bambang Riono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to introduce and train sixth grade elementary school students in Gunungtiga Village, Belik District, Pemalang Regency, in facing the Computer-Based Minimum Competency Assessment (AKM). The implementation method uses a participatory approach through socialization, direct simulation using the official Pusmendik website (https://pusmendik.kemdikbud.go.id/an/simulasi_akm), and technical assistance. The results show that students have a better understanding of literacy and numeracy question formats, are able to operate digital devices, and have increased self-confidence in facing national assessments. This program is beneficial in enhancing students' digital literacy and mental readiness.